A Physiologically Informed Strategy to Effectively Open, Stabilize, and Protect the Acutely Injured Lung - Nieman, Gary F.; Al-Khalisy, Hassan; Kollisch-Singule, Michaela; Satalin, Joshua; Blair, Sarah; Trikha, Girish; Andrews, Penny; Madden, Maria; Gatto, Louis A.; Habashi, Nader M. (Frontiers in Physiology, 2020)
Acute respiratory distress syndrome (ARDS) causes a heterogeneous lung injury and remains a serious medical problem, with one of the only treatments being supportive care in the form of mechanical ventilation. It is very difficult, however, to mechanically ventilate the heterogeneously damaged lung without causing secondary ventilator-induced lung injury (VILI). The injured lung becomes time and pressure dependent, meaning that it takes more time and pressure to open the lung, and it recollapses more quickly and at higher pressure. Current protective ventilation strategies, ARDSnet low tidal volume (LVt) and the open lung approach (OLA), have been unsuccessful at further reducing ARDS mortality. We postulate that this is because the LVt strategy is constrained to ventilating a heterogenous lung with normal and focalized injured tissue, and the OLA, although designed to fully open and stabilize the lung, is often unsuccessful at doing so. In this review we analyzed the pathophysiology of ARDS that renders the lung susceptible to VILI. We analyzed the alterations in alveolar and alveolar duct mechanics that occur in the acutely injured lung and discussed how these alterations are a key mechanism driving VILI. Our analysis suggests that the time component of each mechanical breath, at both inspiration and expiration, is critical to normalize alveolar mechanics and protect the lung from VILI. Animal studies and a meta-analysis have suggested that the time-controlled adaptive ventilation (TCAV) method, using the airway pressure release ventilation mode, eliminates the constraints of ventilating a lung with heterogeneous injury, since it is effective at opening and stabilizing the time- and pressure-dependent lung. In animal studies it has been shown that by “casting open” the acutely injured lung with TCAV we can 1) reestablish normal expiratory lung volume as assessed by direct observation of subpleural alveoli; 2) return normal parenchymal microanatomical structural support, known as alveolar interdependence and parenchymal tethering, as assessed by morphometric analysis of lung histology; 3) facilitate regeneration of normal surfactant function measured as increases in surfactant proteins A and B; 4) significantly increase lung compliance, which reduces the pathologic impact of driving pressure and mechanical power at any given tidal volume.